Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fphar.2022.909123
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress-Related Signature Predicts Prognosis and Drug Response in Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common type of kidney cancer. The maximum number of deaths associated with kidney cancer can be attributed to ccRCC. Disruption of cellular proteostasis results in endoplasmic reticulum (ER) stress, which is associated with various aspects of cancer. It is noteworthy that the role of ER stress in the progression of ccRCC remains unclear. We classified 526 ccRCC samples identified from the TCGA database into the C1 and C2 subtypes by consensus clustering of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…This finding demonstrated that ER stress was suppressed in such patients. 50 The collective observations from previous works, further confirm our conclusion that the anticancer effect of ATF3 is likely mediated through the regulation of the apoptotic signaling pathway in response to ER stress in ccRCC.…”
Section: Discussionsupporting
confidence: 80%
“…This finding demonstrated that ER stress was suppressed in such patients. 50 The collective observations from previous works, further confirm our conclusion that the anticancer effect of ATF3 is likely mediated through the regulation of the apoptotic signaling pathway in response to ER stress in ccRCC.…”
Section: Discussionsupporting
confidence: 80%
“…And another study found that the expression of ATF6, PERK, but not IRE1α, was downregulated in ccRCC patients with advanced tumor stage and grade. This demonstrated ER stress was suppressed in progressive ccRCC patients 43 . The above studies further con rm our conclusion anticancer effect of ATF3 may be achieved through the regulation of apoptotic signaling pathway in response to ER stress in ccRCC.…”
Section: Discussionmentioning
confidence: 89%
“…In the case of hepatocellular carcinoma, the prediction model based on endoplasmic reticulum-related genes showed superior performance (26,27). A surprising association was also found between endoplasmic reticulum stress-related genes and drug therapy in Clear cell renal cell carcinoma (28). Therefore, UCEC patients' prognosis was affected by the endoplasmic reticulum stress-related gene IncRNA signature as well.…”
Section: Discussionmentioning
confidence: 97%